Issues, Challenges and Opportunities of Agriculture in West Kameng District of Arunachal Pradesh (Indian Journal of Extension Education, 2021)
A survey was made during ‘Kisan Jawan Vigyan Mela’ at Defence Research Laboratory Research and Development Centre (DRL R&D Centre), Salari, West Kameng district of Arunachal Pradesh with an aim of getting insight of issues, challenges and opportunities of agriculture sector. The relevant data was collected during Mela from 67 farmers of 11 villages of the district using semi-structured interview (SSI) and a rank-based quotient (RBQ) was worked out to rank the farmers issues and challenges. Based on ranking of problems by the group of farmers, outbreak of insect-pest and diseases, paucity of quality seed material of field and vegetable crops and lack of technical knowhow were found to be the major issues and challenges of the region. The problem solution trees for three of the major problems were constructed and the opportunities in hill farming were suggested to the farmers as per the impact analysis and RBQ.